2012
DOI: 10.4236/ojn.2012.22010
|View full text |Cite
|
Sign up to set email alerts
|

A time to look within curricula—Nursing students’ perception on sexuality and gender issues

Abstract: Nursing students could be viewed as dynamic change agents given the knowledge and skills they would be equipped with. Amongst all areas to be addressed in their clientele of the hospital or community setting, one key area that a nurse could focus on is sexuality. This however is often neglected for simple reasons such as lack of knowledge, embarrassment, fear of intrusion on privacy, or it is perceived as an un-important concern of the patient. Focus groups discussions combined with self report were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This could be explained by the taboo placed on sexuality, which in our study resulted in the uneasiness to address the subject and the lack of attention given to it by both the organization and the nursing team. The lack of attention given by the organization and the nursing team also included the lack of organization of sexuality-related education and thus, insufficient knowledge, resulting in the felt incapability of nurses to address patient sexuality like in other studies [11][12][13]17,18,23,28]. In our study, a part of the taboo comprised certain assumptions about which patient categories were believed to be interested in the subject, such as prejudices regarding the patients' age and sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be explained by the taboo placed on sexuality, which in our study resulted in the uneasiness to address the subject and the lack of attention given to it by both the organization and the nursing team. The lack of attention given by the organization and the nursing team also included the lack of organization of sexuality-related education and thus, insufficient knowledge, resulting in the felt incapability of nurses to address patient sexuality like in other studies [11][12][13]17,18,23,28]. In our study, a part of the taboo comprised certain assumptions about which patient categories were believed to be interested in the subject, such as prejudices regarding the patients' age and sex.…”
Section: Discussionmentioning
confidence: 99%
“…Although barriers regarding addressing patient sexuality have already been widely reported in the past [15,16], a difference between the patients' need for information and the ability of nurses to provide information still exists in modern days. Several studies among nurses working in hospitals in different cultural contexts have found that an important reason why nurses are reserved in discussing the subject is linked with discomfort [12,13,17]. Major reasons for this discomfort are shame, inadequate knowledge, the belief that addressing the subject is improper and not being a topic of priority [11,13,18].…”
Section: Introductionmentioning
confidence: 99%
“…If we focus on sexual competence, it stands out that, in the teaching and learning process in HE in nursing students in part of the countries of the southern area of the European Union (EU) (Spain, Italy, Portugal), there is a standardised curricular dimension guided by a behaviourism based on a biological view of sexuality. Even the theoretical and clinical teaching of sexuality is approached from a reproductive health perspective with scarce and outdated content that does not attract the attention of students [ 19 – 21 ]. Besides, the lack of time and other content priorities place sexuality out of this set, rather on a second tier in nursing classrooms [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nurses need training to improve care and ensure sexuality support to their patients, and to reduce sexual risks in them [ 46 ]. Some research reports that 80% of health professionals are unable to address sexuality in the workplace [ 17 , 20 , 21 ]. Paediatric nursing has long neglected the issue of sexuality, relying on myths that children are asexual.…”
Section: Introductionmentioning
confidence: 99%
“…The same studies show that university curricula are not designed to provide this critical information [11], despite the strong recommendation of the WHO forty years ago. In one study, more than 80% of teachers considered the students unable to address sexuality topics with patients [10,11], and other studies reveal that nursing students give little attention to sexuality subjects [12,13]. Although sexuality is an integral topic in clinical practice, studies suggest a certain level of discomfort among professionals due to lack of knowledge and discomfort and embarrassment in discussing sexuality [14].…”
Section: Introductionmentioning
confidence: 99%